Políticas públicas dirigidas al cuidado infantil en contextos de vulnerabilidad social en la ciudad de Neuquén, una interpelación histórica con perspectiva de género (1970-2013): Public Policies for Child Care in Contexts of Social Vulnerability in the City of Neuquén: A Historical Inquiry with a Gender Perspective (1970–2013) (La Aljaba, Segunda Época. Revista de Estudios de la Mujer, 2025)
AbstractThis article presents recent findings on state intervention in the design of public policies directed toward the care of children in situations of social vulnerability. Drawing on social history with a gender perspective, it examines the political and social context of the city of Neuquén from the 1970s to 2013, with the aim of identifying possible transformations as well as the social actors involved in caregiving work.  Keywords: Public policies – Work – Care – Childhood – Gender – History